India Groundwater Governance Case Study - Garduño, Héctor; Romani, Saleem; Sengupta, Buba; Tuinhof, Albert; Davis, Richard (World Bank, Washington, DC, 2014)
Groundwater comprises 97 percent of the worlds readily accessible freshwater and provides the rural, urban, industrial and irrigation water supply needs of 2 billion people around the world. As the more easily accessed surface water resources are already being used, pressure on groundwater is growing. In the last few decades, this pressure has been evident through rapidly increasing pumping of groundwater, accelerated by the availability of cheap drilling and pumping technologies and, in some countries, energy subsidies that distort decisions about exploiting groundwater. This accelerated growth in groundwater exploitation unplanned, unmanaged, and largely invisible has been dubbed by prominent hydro geologists the silent revolution. It is a paradox that such a vast and highly valuable resource which is likely to become even more important as climate change increasingly affects surface water sources has been so neglected by governments and the development community at a time when interest and support for the water sector as a whole is at an all-time high. This case study is a background paper for the World Bank economic and sector analysis (ESW) entitled too big to fail: the paradox of groundwater governance that aims to understand and address the paradox at the heart of the groundwater governance challenge in order to elevate the need for investing in and promoting proactive reforms toward its management. The project examines the impediments to better governance of groundwater, and explores opportunities for using groundwater to help developing countries adapt to climate change. Its recommendations will guide the Bank in its investments on groundwater and provide the Bank's contributions to the Global Environment Facility (GEF) funded global project groundwater governance: a framework for country action. The case study focused on the national, state and local levels. At the national and state levels, it analyzed the policy, legal, and institutional arrangements to identify the demand and supply management and incentive structures that have been established for groundwater management. At the local level, it assessed the operations, successes, and constraints facing local institutions in the governance of a number of aquifers within peninsula India, on the coast and on the plain of the Ganges river valley.